Logam Berat Timbal (Pb) pada Air dan Plankton di Teluk Benoa, Badung, Bali - Sudarmawan, Ade Riestiari; Suteja, Yulianto; Widiastuti, Widiastuti (Journal of Marine and Aquatic Sciences; Vol 6 No 1 (2020), 2020)
Benoa Bay is the center of estuary of the six rivers in Bali Island. One of the sources of pollution is the input from the river to the waters, especially the liquid waste from the textile industry that contains heavy metals particulary Lead. Moreover, Benoa Bay is a busy area with shipping activities. Shipping activities could direct and indirectly contaminate the waters with Lead from its oil waste. The purposes of this research are to examine the Lead concentration in the surface waters and plankton, and to determine lead bioaccumulation in plankton in the Benoa Bay.  The samplings were conducted on May 2018. Lead concentration in the waters and plankton were analized using Inductively Coupled Plasma Emission (ICPE) with wet destruction method. The result shows that Benoa Bay is heavily contaminated by Lead. According to the Decree of the Minister Environment No. 51 of 2004 about Sea Water Quality Standards, concentration of lead in sea waters is <0.008 mg/L. Concentration of lead in Benoa Bay water surface is 0.001 to 0.053 mg/L and in plankton is 0.001 to 9.287 mg/Kg. It is found that the bioconcentration factor (BCF) of plankton is 593.45. This study emphasize that plankton are able to bioaccumulate Lead.